Proximal migration of a 'double J' ureteric stent in a patient with a staghorn calculus. Issue 12 (28th December 2020) - Burns, Emily J; Smith, Peter M; Liew, Matthew
Abstract: Ureteric stents are widely used for the management of obstructive uropathy and intraoperative identification of the ureters. Despite undergoing numerous modifications since their introduction in 1967, they are frequently associated with complications ranging from irritative symptoms to migration of the stent. Proximal migration of ureteric stents is a relatively uncommon occurrence, with a reported incidence of 1–4.2%; it is usually associated with inappropriate stent length, poor positioning or incorrect deployment of the stent. Here we discuss an interesting case of a patient who unfortunately suffered proximal ureteric stent migration associated with pelvico-ureteric junction obstruction, despite appropriate stent choice, adequate deployment and confirmation of correct positioning. This complication likely occurred secondary to mechanical disruption of the stent caused by the presence of a large staghorn calculus within the renal pelvis.